2011
DOI: 10.1007/s11229-011-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

The psychology and rationality of decisions from experience

Abstract: Most investigations into how people make risky choices have employed a simple drosophila: monetary gambles involving stated outcomes and probabilities. People are asked to make decisions from description. When people decide whether to back up their computer hard drive, cross a busy street, or go out on a date, however, they do not enjoy the convenience of stated outcomes and probabilities. People make such decisions either in the void of ignorance or in the twilight of their own often limited experience of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 80 publications
2
73
1
1
Order By: Relevance
“…The current experiment differs from such studies in several critical respects: First, in our study, outcome probabilities were acquired through trial-by-trial exposure to action-outcome contingencies, rather than being verbally or graphically instructed-substantial behavioral evidence suggests that decisions based on descriptive information can differ quite dramatically from those based on direct experience (Hertwig, 2012). Second, we used instrumental contingencies, whereas in gambling studies decisions are stimulus based, with stimuli being randomly assigned to particular actions on each trial.…”
Section: Discussionmentioning
confidence: 91%
“…The current experiment differs from such studies in several critical respects: First, in our study, outcome probabilities were acquired through trial-by-trial exposure to action-outcome contingencies, rather than being verbally or graphically instructed-substantial behavioral evidence suggests that decisions based on descriptive information can differ quite dramatically from those based on direct experience (Hertwig, 2012). Second, we used instrumental contingencies, whereas in gambling studies decisions are stimulus based, with stimuli being randomly assigned to particular actions on each trial.…”
Section: Discussionmentioning
confidence: 91%
“…This implies that individuals can never learn the objective probabilities and reduce ambiguity completely; however, they are able to decrease the degree of ambiguity and improve the accuracy of their subjectively assigned probabilities by drawing larger samples. The results of existing studies usually show a gap between decisions from description and those from experience (see, e.g., Rakow & Newell, 2010;Hau et al, 2010;Hertwig, 2012), which can be explained in part by sampling errors (see, e.g., Hau et al, 2010). These errors occur because the accuracy of probabilities is lower for smaller sample sizes, as described above.…”
Section: Theory and Predictionsmentioning
confidence: 99%
“…Hertwig andPleskac ( 2008 , 2010 ) proposed one possible advantage that rests on the notion of amplifi cation. Unlike Real ( 1992 ), however, they argued that amplifi cation proffers a cognitive rather than an evolutionary benefi t. Through mathematical analysis and computer simulation, Hertwig and Pleskac ( 2010 ) showed that small samples amplify the difference between the options' average rewards.…”
Section: Fig 82mentioning
confidence: 99%
“…Acknowledgments This text is based largely on Hertwig andHertwig ( 2012 ). We thank Elsevier, Sage, and Springer for granting the permission rights, and the Swiss National Science Foundation for a grant to the fi rst author (100014-126558).…”
mentioning
confidence: 99%